Locomotion and Postural Control in Young Adults with Autism Spectrum Disorders: A Novel Kinesiological Assessment - Riccardo Di Giminiani; Stefano La Greca; Stefano Marinelli; Margherita Attanasio; Francesco Masedu; Monica Mazza; Marco Valenti (Journal of Functional Morphology and Kinesiology)
Background/Objectives: The purposes of the present study were to assess gait by using a novel approach that plots two adjacent joint angles and the postural control in individuals with autism (ASD) and individuals with typical neurodevelopmental (TD). Methods: The surface electromyography (sEMG) activity was measured synchronously with the other variables. Twenty young adult men, 10 with TD and 10 with a diagnosis of ASD, took part in this study. Results: There was a significant difference between ASD and TD groups in the area described by the knee–ankle diagram (p < 0.05). The sEMG activity recorded from the lateral gastrocnemius (LG) during the contact phase of gait was significantly lower in the ASD group compared with the TD group (p < 0.05). The sEMG activity recorded in the different postural conditions showed differences in LG and tibialis anterior (TA) between the ASD and TD groups (p < 0.05). Conclusions: The knee–ankle diagram provided a sensitive and specific movement descriptor to differentiate individuals with ASD from individuals with TD. The reduced LG activation is responsible for the reduced area in the knee–ankle diagram and ‘toe-walking’ in individuals with ASD and represents the common denominator of an altered ankle strategy during locomotion and postural control.